ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007-2011 - Fatoni Hidayat, Riza; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to explore factors that affect capital structure. Optimalization of capital structure required to enhance value of the firm. Based on pecking order theory and trade-off theory, variables that allegedly affect capital structure are sales growth, non-debt tax shield and debt service capacity. Population of this research is manufacturing companies listed on Indonesian Stock Exchange during 2007-2011. Data obtained from financial reports and ICMD (Indonesian Capital Market Directory). Sampling methods using purposive sampling and methods of analysis using multiple linear regression. This study used two models. Model I examines relationship between positive growth of sales and capital structure. Model II examines the relationship between negative growth of sales and capital structure. The results showed positive growth of sales positively effect on capital structure, but negative growth of sales doesn’t appear to be significant. Non-debt tax shield showed no significant effect on both models. Debt service capacity negatively effect on both models.